Ethical dimension of the professional formation in health: a case study - João Carlos Caetano; Mirelle Finkler; Flávia Regina Souza Ramos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The study is a PhD thesis based on a qualitative research regarding the ethical dimension of the professional formation, which took as study subject the process developed in dentistry courses at the Brazilian universities. A conceptual basis was built up considering the complexity of factors which have influence on the ethical formation searching to guide the different steps of the data gathering: a questionnaire application in 15 dentistry courses; from those 2 will be selected for a deeper research which consists of interviews, observations and focal groups. The results will contribute in the construction of knowledge related to the required changes seeking to construct ethically skilled professionals that will cope with the society's deman